The Parliamentary Office of Science and Technology: Connecting the UK Parliament with Research Evidence (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
The Parliamentary Office of Science and Technology (POST) has connected the UK Parliament with impartial research evidence for over 35 years. This article outlines POST’s structure, methodology, and services – including briefings, expert access, and confidential enquiries – that support evidence-informed policymaking. It highlights POST’s role in overcoming barriers to research use in parliament, its collaboration with academia, and its impact on parliamentary work, especially committee scrutiny. The paper also explores future developments, including rapid evidence synthesis and AI tools, aimed at enhancing responsiveness and efficiency in meeting growing parliamentary demand for trusted research.
Keywords: evidence-informed policymaking; parliamentary research; knowledge exchange; science and technology advice; legislature support services